Co-evolution of affinity and stability of grafted amyloid-motif domain antibodies. Issue 10 (19th September 2015) - Julian, Mark C.; Lee, Christine C.; Tiller, Kathryn E.; Rabia, Lilia A.; Day, Evan K.; Schick, Arthur J.; Tessier, Peter M.
Abstract : An attractive approach for designing lead antibody candidates is to mimic natural protein interactions by grafting peptide recognition motifs into the complementarity-determining regions (CDRs). We are using this approach to generate single-domain ( V H ) antibodies specific for amyloid-forming proteins such as the Alzheimer's Aβ peptide. Here, we use random mutagenesis and yeast surface display to improve the binding affinity of a lead V H domain grafted with Aβ residues 33–42 in CDR3. Interestingly, co-selection for improved Aβ binding and V H display on the surface of yeast yields antibody domains with improved affinity and reduced stability. The highest affinity V H domains were strongly destabilized on the surface of yeast as well as unfolded when isolated as autonomous domains. In contrast, stable V H domains with improved affinity were reliably identified using yeast surface display by replacing the display antibody that recognizes a linear epitope tag at the terminus of both folded and unfolded V H domains with a conformational ligand (Protein A) that recognizes a discontinuous epitope on the framework of folded V H domains. Importantly, we find that selection for improved stability using Protein A without simultaneous co-selection for improved Aβ binding leads to strong enrichment for stabilizing mutations that reduce antigen binding. Our findings highlight the importance of simultaneously optimizing affinity and stability to improve the rapid isolation of well-folded and specific antibody fragments.